Analisis Kepuasan Donatur dengan Metode Customer Satisfaction Index (CSI) pada Lembaga Manajemen Infaq (LMI) - Annisa Andra Azifa; Agil Darmawan (Sekolah Tinggi Ilmu Ekonomi Syariah Nahdlatul Ulama Bengkulu, 2026)
This study aims to analyse the level of satisfaction among retail donors at the Infaq Management Institution (LMI) using the Customer Satisfaction Index (CSI), Customer Effort Score (CES) and Net Promoter Score (NPS) approaches. The method employed was a quantitative survey of LMI retail donors to measure perceptions of service ease, satisfaction levels and loyalty. The results of the study indicate that the CES score of 3.58 (on a scale of 4) falls within the ‘excellent’ category, meaning that the donation process through to reporting has been straightforward and efficient. Furthermore, the CSI score of 4.62, or 92.4%, indicates that donor satisfaction is in the ‘very satisfied’ category and has exceeded the minimum satisfaction standard. Meanwhile, the NPS score of 28% falls into the ‘good’ category, indicating that donors are inclined to recommend LMI, although there remains scope to improve loyalty to a higher category. The research findings also indicate donor preferences and behaviours that need to be accommodated through a more personalised service approach, as well as a high level of donor interest in participating in distribution activities. Therefore, enhancing engagement strategies and developing collaborative programmes are strategic steps that can be taken to sustainably improve donor satisfaction and loyalty.